Prevalence of xerostomia on type 2 diabetes mellitus in Hajj Hospital Surabaya - Kus Harijanti; Bagus Soebadi; Irvanda Mulyaningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Diabetes Mellitus (DM) is a chronic disorder of carbohydrate, fat and protein metabolism. A defective or deficient of the insulin secretory, which is translated into impaired carbohydrate (glucose) use, is characteristic feature of DM, as the resultant is hyperglycemia. There is variability among patients, however, morphologic changes are likely found in arteries (atherosclerosis), basement membrane of the blood vessel wall tissues (micro angiopathy), kidneys (diabetic nephropathy), retina (retinopathy), nerves (neuropathy) and other tissues. If it involves salivary glands, the clinical sign is xerostomia. The type 2 of DM is caused by a combination of peripheral resistance to insulin action and an inadequate secretory response of the pancreatic b-cell. Approximately 80% to 90% of patients have type 2 diabetes. The purpose of this study was to determine the prevalence of xerostomia and its relation with level of blood glucose in type 2 DM. The data was taken using cross sectional method on the diabetic patients of Internal Medicine clinic, Hajj Hospital Surabaya from February to March 2006. The result that showed among 50 samples of the type 2 DM, the prevalence of xerostomia were 38 patients (76%). Most of the patients (32 patients = 84%) on bad regulation of DM with level of fasting glucose ≥ 126 mg/dl and level of post prandial glucose ≥ 180 mg/dl. The study showed that bad regulation of type 2 DM could develop complication on salivary glands, with xerostomia as the clinical sign.